2023
DOI: 10.3389/fpsyt.2023.1113356
|View full text |Cite
|
Sign up to set email alerts
|

An interdisciplinary multimodal integrative healthcare program for depressive and anxiety disorders

Abstract: ObjectiveAlthough multimodal interventions are recommended in patients with severe depressive and/or anxiety disorders, available evidence is scarce. Therefore, the current study evaluates the effectiveness of an outpatient secondary care interdisciplinary multimodal integrative healthcare program, delivered within a transdiagnostic framework, for patients with (comorbid) depressive and/or anxiety disorders.MethodsParticipants were 3,900 patients diagnosed with a depressive and/or anxiety disorder. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…We then tried to confirm and extend these findings using simulations based on real data from a similar previous study conducted by Dominguez-Rodriguez et al (2021, 2023. The data included the results of 114 participants, 45 on the treatment condition and 69 on the control condition, which after finishing a waiting period of 36 days, were assigned to the treatment condition.…”
Section: Sample Sizementioning
confidence: 95%
See 1 more Smart Citation
“…We then tried to confirm and extend these findings using simulations based on real data from a similar previous study conducted by Dominguez-Rodriguez et al (2021, 2023. The data included the results of 114 participants, 45 on the treatment condition and 69 on the control condition, which after finishing a waiting period of 36 days, were assigned to the treatment condition.…”
Section: Sample Sizementioning
confidence: 95%
“…Furthermore, meta-analyses have revealed that self-applied internet interventions are effective at reducing both depression and anxiety symptomatology and increasing well-being ( Pang et al, 2021 ; Ye et al, 2022 ). Specifically, the treatment components shown to be effective when applied online are Acceptance and Commitment Therapy ( Thompson et al, 2021 ), Cognitive Behavioral Therapy ( Morgan et al, 2017 ), Mindfulness ( Spijkerman et al, 2016 ), and Behavioral Activation ( Huguet et al, 2018 ), also, multicomponent proposals ( Marcelle et al, 2019 ; Wijnen et al, 2023 ). Other approaches from ITLAS group have demonstrated the effectiveness of multimodal interventions in the Latino population for grief treatment ( Dominguez-Rodriguez et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…MPT can be used to treat a wide range of diseases. It has been evaluated for chronic back pain, fibromyalgia, facial pain, depression and other clinical pictures [38][39][40].…”
Section: Of 18mentioning
confidence: 99%